Effective leadership in public relations in Latin America. The role of empathy for employee engagement. - Sadi, Gabriel; Álvarez-Nobell, Alejandro; Barroso, María-Belén (My University, 2023)
During Covid-19 and in response to the demands of younger generations, many leaders in organizations could have changed their communication style and humanized the way they interact. This paper aims to understand the role of empathy in communication leadership and its effect in the work environment for Latin American PR practitioners. This study relies on several theories that suggest that the ability to have and show empathy is an important part of effective and servant leadership (Spears, 2002). Empathy enables leaders to show individualized levels of consideration to followers (e.g. Avolio and Bass, 1995), recognise the emotions of others (Rubin et al., 2005) and be aware of both self and context (Walumbwa et al., 2008). In addition, empathic communication allows leaders to connect with and respond to different stakeholders (Dolamore, 2019). Measures of empathy are adapted from the Emotional Competence Inventory (Boyatzis et al., 2000). A survey dataset has been collected from practitioners in 20 Latin American countries (N=1,345), using SPSS for data analysis. The results show an increasing projection of empathy levels, and a correlation between the application of empathy in communication leadership and employee engagement.
Liderazgo efectivo en las relaciones públicas de América Latina. El rol de la empatía en el compromiso de los empleados
Keywords: Gestión de personal - Aspectos psicológicos; Liderazgo; América Latina; Relaciones públicas